2019
DOI: 10.1055/s-0039-3402428
|View full text |Cite
|
Sign up to set email alerts
|

The Central Role of Fibrinolytic Response in Trauma-Induced Coagulopathy: A Hematologist's Perspective

Abstract: Severe trauma is the leading cause of death globally. Though improved resuscitation, particularly early initiation, has reduced the 24-hour mortality rate, the overall morbidity and 30-day mortality remain high mostly due to massive hemorrhage and head injury in the early stages and sepsis and multiorgan failure later on. With recent clinical trials of antifibrinolytic treatment with tranexamic acid, and with the observations that fibrinolytic activity varies widely among the injured patients, the role of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 106 publications
0
22
0
Order By: Relevance
“…Another study revealed that elevated levels of the PAI-1/tPA complex were related with disease severity and could be considered an independent risk factor for death in patients with COVID-19 [ 90 ]. By affecting multiple organs, including the lung as the predominant target, the formation of microthrombi in these organs may lead to multiorgan failure [ 91 ]. In this respect, the efficacy, i.e., an improved clinical outcome, a lower degree of organ failure, decreased PAI-1 levels, and ventilator free days, as well as the safety of a small molecule PAI-1 inhibitor, TM5614, are currently investigated in a phase 1/2 clinical trial for high-risk patients hospitalized with severe COVID-19 ( : NCT04634799).…”
Section: Role Of Pai-1 In Diverse Pathologiesmentioning
confidence: 99%
“…Another study revealed that elevated levels of the PAI-1/tPA complex were related with disease severity and could be considered an independent risk factor for death in patients with COVID-19 [ 90 ]. By affecting multiple organs, including the lung as the predominant target, the formation of microthrombi in these organs may lead to multiorgan failure [ 91 ]. In this respect, the efficacy, i.e., an improved clinical outcome, a lower degree of organ failure, decreased PAI-1 levels, and ventilator free days, as well as the safety of a small molecule PAI-1 inhibitor, TM5614, are currently investigated in a phase 1/2 clinical trial for high-risk patients hospitalized with severe COVID-19 ( : NCT04634799).…”
Section: Role Of Pai-1 In Diverse Pathologiesmentioning
confidence: 99%
“…In turn, improved hemostatic monitoring and personalized anticoagulation may confirm the hypothesis that early therapeutic anticoagulation for patients with CAC may prevent deterioration and thrombohemorrhagic manifestations simultaneously, so long as intensive bedside precisionbased medicine is used to guide anticoagulation with VETs as well as the common coagulation tests. 4,10,11 "SPECTRUM OF INQUIRY": THE LARGE RCTs VS SMALL HYPOTHESIS-GENERATING OBSERVATIONAL STUDIES OF PRECISION-BASED MEDICINE Finally, this review addresses the important epistemologic question regarding the significance of smaller hypothesisgenerating studies based on clinical observation and mechanistic rationale, particularly during a period of early scientific discovery such as the SARS-CoV-2 pandemic. [12][13][14] Rapid deployment of the 3 mpRCTs concerning therapeutic anticoagulation in the COVID-19 patient is an example of pandemic-response, research-based rapid innovation.…”
Section: Covid-19 Patients In Fibrinolysis Shutdown Clot and Bleed At The Same Timementioning
confidence: 99%
“…2 Meizoso and coauthors, 1 other critical care trauma surgeons, and nonsurgical medical colleagues, have applied their knowledge and experience with fibrinolysis shutdown in trauma-induced coagulopathy, sepsis-induced coagulopathy, and now CAC, where it is a nearly ubiquitous finding on presentation and a consistent marker of disease severity. 3,4 This brief and accurate review highlights and clarifies the following similarities between trauma and sepsis and the significance of CAC within the context of the fibrinolytic spectrum.…”
mentioning
confidence: 97%
“…Thus, it can be seen that during the course of COVID-19, these components of the fibrinolytic system, especially uPA in its various forms and PAI-1 will influence the amount of plasmin generation and the ensuing D-dimer formation. 14,15 A full understanding of the complex interactions of active PAI-1, scuPA, tcuPA, uPAR and suPAR in the generation of active plasmin in involved organs in COVID-19 is essential in explaining the utility of D-dimer level as a biomarker in assessing the severity of the disease. How D-dimer values may assist in the management of anticoagulation in COVID-19 remains to be investigated.…”
Section: Accepted Manuscriptmentioning
confidence: 99%